An audit of medical documentation on standardised electronic neonatal database (SEND) in a large level-2 neonatal unit. (7th June 2011) - Kathirgamathamby, V; Pitts, J; Perry, R; Kurre, M; Das, A
Abstract : Background: Our unit uses the web-based live patient management system, Standardised Electronic Neonatal Database (SEND), also known as UK national Neonatal System, for medical documentation during all neonatal inpatient admissions. Standards: We audited our documentation standards against those set by the Academy of Medical Royal Colleges. These generic standards are developed by the Health Informatics Unit working with NHS connecting for health and published by Royal College of Physicians. Methods: A retrospective audit of all admissions to Queen's Hospital Neonatal Unit during January 2009–October 2010 (22 months).Total 1061 electronic patient documentations on SEND were reviewed. Results: Results were analysed under sections-maternal and baby demographics, maternal obstetric details, delivery and resuscitation, admission and discharge summary, daily level of care data and NNAP events. Completion of data is noted as follows: maternal surname, date of birth, address-100%, GP details-94%, maternal ethnicity-81%, baby's date and time of birth, birth order, birth weight, sex and gestation-100%, mode of delivery-97%, antenatal steroid-95%, maternal medical history-80%, past obstetric history-84%, LMP-75%, EDD-84%, complications during pregnancy-80%, maternal serology and scan findings-90%, baby's reason for admission-86%, source of admission-90%, resuscitation details-93%, Apgar scores-97%, routine examination on admission-37%, routine screening, immunisation-44–69%, NNAP data items-54–93%, problem list at discharge-86%, short summary of stay-94%, feeding at discharge-91%, discharge address-100%, completed level of care days-91%. Conclusion: Good medical record keeping standards demonstrated in many areas. Improvement necessary in recording newborn examination, routine screening and some NNAP items. We recommend continued in-house training and supervision on this and re-audit.